The Effect Of Coaching And Mentoring On Work Motivation By Mediating Employee Self-Efficacy In Sijunjung Regency - Jurniati, Novita; Uripan, Koen Irianto; Soleha, Siti Nur; Endriatmoko, Yosa; Suminar, Lintang (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The era of digital transformation and the complexity of modern organizational performance demands encourage the application of coaching and mentoring as a human resource development strategy. This study analyzes the influence of coaching and mentoring on the work motivation of employees in Sijunjung Regency, with self-efficacy as a mediator. The phenomenon in the field shows a disparity in work motivation between employees who participate in coaching and mentoring programs and those who do not, where the first group has higher self-efficacy and work motivation. A quantitative approach with an explanatory causality method was used on 125 employees through purposive sampling. Data was collected with a 5-point Likert scale questionnaire and analyzed using PLS-based SEM via SmartPLS. The results showed that coaching had a significant effect on work motivation (β = 0.711) and self-efficacy (β = 0.820), while mentoring had a significant effect on work motivation (β = 0.904) and self-efficacy (β = 0.856). Self-efficacy also mediates the influence of coaching and mentoring on work motivation. The research model showed R² 0.754 for self-efficacy and 0.044 for work motivation with a Q² of 0.996, indicating excellent predictive relevance. The findings affirm the important role of self-efficacy as a mediator and make theoretical and practical contributions to human resource development in local governments.